Agronomic Optimum Seeding Rate for Irrigated Maize in Texas is Concomitant to Growing Season Mean Daily Minimum Temperature. Issue 4 (27th December 2012) - Thompson, W. H.; Pietsch, D.; Blumenthal, J. M.; Ibrahim, A. M. H.; Baltensperger, D. D.
Abstract Our study was conducted to determine agronomic optimum seeding rates (AOSR) for irrigated maize under a range of agroecological conditions in Texas. Environmental factors that affect irrigated maize production vary considerably across Texas. This variability imposes region‐specific limitations on statewide maize seeding rate recommendations. Our research examined the efficiency of varying seeding rates on irrigated maize grain yields in five USEPA Level IV Ecoregions that comprise most of the irrigated maize‐producing area of Texas. The selected sites span a distance of 1200 km from south to north Texas and elevations from 20 to 1218 m above mean sea level. We conducted the study over three growing seasons from 2005 through 2007 in two Level IV Ecoregions of the High Plains of North Texas (N), one in the East Central Plains (E), one in the Southern Plains and one in Western Gulf Coastal Plains of South Texas (S). We observed that maximum grain yields and AOSR to achieve maximum maize grain yields vary considerably among ecoregions. In South Texas, we observed grain yield response rates of 125–129, 151 kg 1000 seeds−1 in E and 163–199 kg 1000 seeds−1 in N. We show that growing season average daily minimum air temperature (TMIN) explains most of this variation (r2 = 0.98, P‐value < 0.01) and conclude that seeding rate efficiency is concomitant to TMIN. Maximum grain yields (GYMAX) determined with seeding rate response analysis also varied among ecoregions and with TMIN from south to north Texas, from a low of 8.3 Mg ha−1 in S to a high of 18.4 Mg ha−1 in N (r2 = 0.59, P‐value < 0.01). We conclude that development of agronomic management models by Level IV Ecoregions of Texas combined with site‐specific TMIN climatological data serve as a valid template for delivering robust and agroecozone‐specific irrigated maize seeding rate recommendations in Texas.